George Hoyningen-Huene photography, fashion, film - Brown, Susanna (Thames & Hudson, 2024)
Baron George Hoyningen-Huene (1900–1968), known simply as Huene, worked during the golden age of couture fashion and Hollywood cinema. He was born in St Petersburg to a wealthy family, but they had to flee their home during the Russian revolution in 1917. Huene spent time in England before moving to Paris, where he was employed to create photographs for Vogue and Vanity Fair and rapidly established himself as a visual innovator, fusing elements of neoclassicism and surrealism to create chic, arresting images. In 1935, Huene joined Harper’s Bazaar magazine, where he remained a contributor until 1946, following which he settled in California and embarked on a second career as a colour coordinator for Hollywood films. Supported by an international exhibition opening at Chanel Nexus Hall in Tokyo, this book combines elegant design and production values with rigorous new research and scholarship. Organized into eight chapters, each supported by texts by contributing writers from the worlds of fashion, cinema and photography, and featuring names and faces that have defined our view of style, glamour and grace in the 20th century, it reminds us of Huene’s position among the greats of photography
Keywords: Hoyningen-Huene, George -- 1900-1968; Bildband